The Influence of Parent Parenting Patterns on Student Learning Achievement - Esteran Damanik; Rini Sugiarti; Erwin Erlangga (CV. Rayyan Dwi Bharata, 2023)
Abstract. Every parent dreams of children who always get very good achievements, both in the school environment and outside of school. To get good achievements, of course, cannot be separated from parental support, how parents nurture and educate children so that children can develop well and get good achievements too. At an early age is the right time to develop all aspects of development because children experience the process of growing and developing rapidly. The family is the first social environment that individuals encounter since they were born into the world, therefore the role of parents is very influential for children to get good development, both physically and academically. The purpose of this study is to find out how the influence of parenting patterns on children's learning achievement in grades 4 5 of EFATA Elementary School in Baloi Permai, Batam. The method used in this research is descriptive qualitative with data collection techniques using interviews, observation, and documentation, after which it is processed through data triangulation. The population of this study were parents of students from grades 4 5 at EFATA school. Based on the results of this study, it shows that there is an influence of parenting patterns on student learning achievement at school, good parenting has a big influence on increasing student learning achievement. The conclusion of this research is that of the four types of parenting patterns, only one is significant.